Adverse effects of antiretroviral treatment at a tertiary care hospital in India: a prospective observational study - Vaghani, Sweta V.; Gagiya, Ashok K.; Shukla, Deepak K.; Patel, Vishal P. (International Journal of Research in Medical Sciences, 2017)
Background: Data on adverse drug reactions (ADRs) related to antiretroviral (ARV) use in public health practice are few indicating the need for antiretroviral therapy (ART) safety surveillance in clinical care. Methods: 143 patients on ART were studied prospectively over a period of two years. All patients were asked to visit the clinic if they developed any symptoms or on a monthly basis. They were screened clinically and investigated suitably for any ADRs. Results: 143 HIV positive patients were analyzed. At least one ADR was seen in 87 (60.83%) subjects. The most common ADR observed was peripheral neuropathy in 54 (37.76%) patients, followed by lipodystrophy (13.98%), anemia (10.48%) and hyperlipidemia (6.29%). Patients with peripheral neuropathy and lipodystrophy were mainly on stavudine based regimes, while patient with anemia and hyperlipidemia were on zidovudine based regimes. Conclusions: In spite of high ADRs, highly active antiretroviral therapy (HAART) is the only answer to HIV/AIDS. To optimize adherence and thus, efficacy of ART, clinicians must focus on preventing adverse effects whenever possible, and distinguish those that are self-limited from those that are potentially serious.